2006
DOI: 10.1002/pd.1510
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and attitude toward prenatal diagnosis of chromosomal abnormalities in patients with no access to legal termination of pregnancy

Abstract: In many countries, prenatal genetic testing is offered, but TOP is not available. In the present study, although most of the couples who decided to undergo prenatal genetic testing were aware of this, they still chose to perform prenatal diagnosis. The main reason given was to obtain reliable information about fetal condition. Finally, if a fetal chromosomal abnormality were detected, most of them would consider TOP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 35 publications
0
13
0
3
Order By: Relevance
“…For example, a 1991 study showed that 89 per cent of couples in Pakistan known to be carrying a fetus affected with an inherited hemoglobin disorder chose to terminate the pregnancy (Ahmed et al 1991). A survey in Argentina and Uruguay, where abortion on the grounds of fetal abnormality is illegal, indicated that 68.2 per cent of couples undergoing prenatal diagnosis would contemplate termination of pregnancy in cases of serious congenital abnormality (Gadow et al 2006). A recent retrospective study of 207 cases in Uruguay provides the first concrete data from a Latin American country.…”
Section: Termination For Fetal Abnormalitymentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a 1991 study showed that 89 per cent of couples in Pakistan known to be carrying a fetus affected with an inherited hemoglobin disorder chose to terminate the pregnancy (Ahmed et al 1991). A survey in Argentina and Uruguay, where abortion on the grounds of fetal abnormality is illegal, indicated that 68.2 per cent of couples undergoing prenatal diagnosis would contemplate termination of pregnancy in cases of serious congenital abnormality (Gadow et al 2006). A recent retrospective study of 207 cases in Uruguay provides the first concrete data from a Latin American country.…”
Section: Termination For Fetal Abnormalitymentioning
confidence: 99%
“…Some people who undergo prenatal diagnosis choose to continue a pregnancy even if serious fetal abnormality is detected (Gadow et al 2006;Rapp 1999). However, research and experience indicate that many women carrying a fetus affected by a serious and 'untreatable' congenital disorder prefer to terminate the pregnancy.…”
Section: Termination For Fetal Abnormalitymentioning
confidence: 99%
“…Thus, they have access to genetic counseling, prenatal screening, and prenatal diagnosis. 15,16 Patients from lower socioeconomic groups attend public hospitals, most of them free or with very low costs. These mothers are younger, with lower education levels and lower numbers of prenatal visits.…”
mentioning
confidence: 99%
“…According to Gadow et al, 24 in 2006, in a study conducted in Argentina -a country where termination of pregnancy after the diagnosis of chromosomal abnormality is not legally permitted -with 372 couples during counseling prior to the invasive procedure for fetal karyotyping, 68% of couples thought about terminating the pregnancy despite the practice being illegal and the mother being exposed to unsafe methods of abortion. In the same study, 87% of couples reported that the main reason for wishing to have access to a prenatal diagnosis is to receive accurate information about the health of the fetus, regardless of the possibility of termination.…”
Section: Discussionmentioning
confidence: 99%
“…In these cases, about 60-90% of parents choose to terminate the pregnancy after receiving the diagnosis of the abnormality. [22][23][24] In Brazil, the current legislation does not provide permission for termination of a pregnancy in cases of chromosomal abnormalities, and this practice is typified in the country's Criminal Code. There are favorable judicial decisions for termination in the case of anomalies incompatible with life.…”
Section: Introductionmentioning
confidence: 99%